Air-blast anti-fouling cleaning for aquatic optical sensors - Yali, Zhang; Zhang, Naiqian (International Journal of Agricultural and Biological Engineering, 2015)
In order to solve the problem of fouling of submerged optical instruments, an air-blast cleaning mechanism was integrated into an optical sensor used for measuring suspended sediment concentration (SSC) in natural waters. Laboratory experiments in a manually created fouling environment were conducted to observe the fouling process on sensor cases made of different materials, and to verify the effectiveness of air-blast cleaning in reducing fouling. Results indicated that sensors with an aluminum case experienced more serious bio-fouling than that with polyethylene case, and the air-blast cleaning mechanism was capable of reducing fouling effect on sensor signals. So the submerged optical instruments should avoid using metal materials. The duration and frequency of air-blast cleaning can be determined and adjusted depending on actual field conditions.Keywords: optical sensor, aquatic sensor, anti-fouling, bio-fouling, air-blast cleaning, sediment DOI: 10.3965/j.ijabe.20150806.1853Citation: Zhang Y L, Zhang N Q. Air-blast anti-fouling cleaning for aquatic optical sensors. Int J Agric & Biol Eng, 2015; 8(6): 128－135.